1991
DOI: 10.1002/bies.950130902
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis for tropomyosin isoform diversity

Abstract: The tropomyosins are a family of actin filament binding proteins. In multicellular animals, they exhibit extensive cell type specific isoform diversity. In this essay we discuss the genetic mechanisms by which this diversity is generated and its possible significance to cellular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
276
0
8

Year Published

1994
1994
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 341 publications
(289 citation statements)
references
References 48 publications
5
276
0
8
Order By: Relevance
“…T ropomyosin is an actin-binding protein found in virtually all eukaryotic cells (1). In sarcomeric muscle it acts together with troponin to regulate myosin access to the actin filament (2).…”
mentioning
confidence: 99%
“…T ropomyosin is an actin-binding protein found in virtually all eukaryotic cells (1). In sarcomeric muscle it acts together with troponin to regulate myosin access to the actin filament (2).…”
mentioning
confidence: 99%
“…Tropomyosin isoform expression involves the use of multiple genes, but diversity is also generated by alternative processing of mRNA (Lees-Miller and Helfman, 1991). Four different tropomyosin genes have been characterised in mammals (a-TM, fl-TM, and hTMnm).…”
mentioning
confidence: 99%
“…It has been suggested that down-regulation of tropomyosin expression in tumour cells may decrease microfilament stability owing to increased susceptibility to depolymerising factors. The loss of microfilament structure may lead to altered cell shape, motility and altered interaction with extracellular supporting elements (Cooper et al, 1987;Lees-Miller and Helfman, 1991). Interestingly, forced expression of tm 1 or tm 2 in tumour cells by the introduction of cDNA expression vectors suppresses malignant growth (Prasad et al, 1993) or causes an altered cellular morphology (Takenaga and Masuda, 1994).…”
mentioning
confidence: 99%
“…Such cross-linked heterodimers occur in muscle cells (Lehrer and Joseph, 1987) because the tropomyosin p isoform of muscle cells contains both Cys36 and Cysl90 which would permit their formation. The observation raises the possibility that NIH3T3 cells express, in addition to the high-M, isoforms typical of fibroblasts, a significant amount of an alternative splice product (Lees-Miller and Helfman, 1991) typical of muscle cells. Since, as noted below, this form was produced to a much lower degree in other normal fibroblasts, its prominence in NIH3T3 cells may be a peculiarity of that cell line, or of the particular cultivar used in our laboratory.…”
Section: Tropomyosin Dimer Formation In Cultured Fibroblastsmentioning
confidence: 98%
“…Tropomyosins are a family of ubiquitous actin-binding proteins with extensive a-helical structure that play a welldefined role in muscle contraction (Leavis and Gergely, 1984 ;Payne and Rudnick, 1985 ;Lees-Miller and Helfman, 1991). In non-muscle cells, the role of tropomyosins is less clearly understood, and it is generally thought that they are involved in stabilization of actin microfilaments which, in turn, play an important role in maintaining cell shape, motil-ity, and interaction with extracellular supporting elements (Pollard et al, 1976;CBtC, 1983;Stossel et al, 1985).…”
mentioning
confidence: 99%